Proceedings of the 37th International Symposium on Archaeometry, 13th-16th May 2008, Siena, Italy - Turbanti-Memmi, Isabella (Springer, 2011)
The book contains the Proceedings of the 37th International Symposium on Archaeometry, 12th May 2008, Siena, Italy. The aim of the Symposium is to promote the development and use of scientific techniques in order to extract archaeological and historical information from cultural heritage and the paleoenvironment. It involves all Natural Sciences and all types of objects and materials related with human activity. The papers deal with the development and/or application of scientific techniques for extracting information related to human activities of the past, including the biological nature of.